Comparative analysis of hybridized solutions to water resources management in Burkina Faso, India and Peru. Issue 1 (2nd January 2021) - Everard, Mark; Loayza Muro, Raul; Bunclark, Lisa; Taboada, Rossi
ABSTRACT: Hybridization of 'green' and engineered infrastructure, informed by protecting or restoring catchment processes, can resolve interconnected demands on catchment ecosystems, potentially also reversing historic degradation of socio-ecological systems. Pressures are acute in water-scarce, developing regions with episodic rainfall, exacerbated by historic presumptions favouring engineered management. Comparing conditions, histories and emerging approaches in contrasting regions – the Central Plateau of Burkina Faso, Rajasthan State (India) and Ayacucho Region (Peru) – reveals similar yet distinct approaches reflecting different starting regimes. Transferrable learning about hybridizing localized, nature-based solutions and engineered technology informs the necessary transition towards a sustainable approach in these and other regions.